Two New Species of Mites of the Genus Scutacarus (Acari, Heterostigmata, Scutacaridae) from Ukraine - Khaustov, A.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Two new species of mites of the genus Scutacarus Gros, 1845 of spengleri-group: S. yuliae Khaustov, sp. n. and S. livshitsi Khaustov, sp. n. are described from Ukraine.